2002
DOI: 10.1016/s0886-3350(02)01294-4
|View full text |Cite
|
Sign up to set email alerts
|

Management of retinal detachments in pseudophakic patients with Artisan lenses

Abstract: In most cases, the Artisan lens did not significantly limit peripheral retinal visibility. Standard buckling procedures were generally successful. Given the limited support provided by the iris, the presence of gas in the vitreous cavity can lead to anterior displacement of the lens. Corneal endothelial touch can be prevented by the use of Healon, which is sufficient if short-term gas tamponade is used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 13 publications
1
8
0
Order By: Relevance
“…2 Successful RD repair occurs at the same rate in patients with Artisan IOLs and those with PC IOLs. 23 With an incidence of RD between 3% and 18% after removal of a dropped nucleus, careful examination of the peripheral retina is advisable, particularly in the first 2 to 3 months. [24][25][26][27][28][29][30][31][32] The older iris-plane lenses severely limited pupil dilation.…”
Section: Discussionmentioning
confidence: 99%
“…2 Successful RD repair occurs at the same rate in patients with Artisan IOLs and those with PC IOLs. 23 With an incidence of RD between 3% and 18% after removal of a dropped nucleus, careful examination of the peripheral retina is advisable, particularly in the first 2 to 3 months. [24][25][26][27][28][29][30][31][32] The older iris-plane lenses severely limited pupil dilation.…”
Section: Discussionmentioning
confidence: 99%
“…Although the problem may be reduced visualization of retina, especially in traumatic patients with posterior segment injury, it has been noted that the Artisan implantation does not significantly interfere with adequate visualization of peripheral retina for vitreoretinal surgery. 18 However, given the limited support provided by the iris, the presence of gas in the vitreous cavity can lead to the anterior displacement of the lens. van der Meulen 18 suggested that corneal endothelial touch can be prevented by the use of Healon.…”
Section: Complicationsmentioning
confidence: 99%
“…18 However, given the limited support provided by the iris, the presence of gas in the vitreous cavity can lead to the anterior displacement of the lens. van der Meulen 18 suggested that corneal endothelial touch can be prevented by the use of Healon.…”
Section: Complicationsmentioning
confidence: 99%
“…Macular pucker develops in 3 % [ 85 ]. Given the limited support provided by the iris after cataract surgery, the presence of intravitreal gas has been shown to cause anterior displacement of Artisan intraocular lenses [ 52 ].…”
Section: A Resultsmentioning
confidence: 99%
“…PR usually fails in RRD following vitrectomy for posteriorly dislocated lens fragments and requires subsequent scleral buckling [ 51 ]. PR has also been reported to cause anterior displacement of Artisan intraocular lenses [ 52 ].…”
Section: Contraindications For Pneumatic Retinopexymentioning
confidence: 99%